Answer:
([tex]\frac{13}{5}[/tex] , [tex]\frac{6}{5}[/tex] )
Step-by-step explanation:
Given the 2 equations
2x - y - 4 = 0 → (1)
3x + y - 9 = 0 → (2)
Adding the 2 equations term by term will eliminate the term in y, thus
5x - 13 = 0 ( add 13 to both sides )
5x = 13 ( divide both sides by 5 )
x = [tex]\frac{13}{5}[/tex]
Substitute this value into either of the 2 equations and evaluate for y
Substituting into (2)
[tex]\frac{39}{5}[/tex] + y - 9 = 0
- [tex]\frac{6}{5}[/tex] + y = 0 ( add [tex]\frac{6}{5}[/tex] to both sides )
y = [tex]\frac{6}{5}[/tex]
Solution is
([tex]\frac{13}{5}[/tex] , [tex]\frac{6}{5}[/tex] )